EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS FLASH DALAM MEMBACA TEKS PROSEDUR KOMPLEKS PADA SISWA KELAS X SMK NEGERI 1 SEWON - Deni Setiawan; Siti Rochmiyati (Universitas Sarjanawiyata Tamansiswa, 2015)
ABSTRACTÂ The purpose of this research is descriptive (1) know the tendency of the learning achievement read students of class X SMK Negeri 1 Sewon which used learning media based on PowerPoint; (2) which used learning media based on Flash. Comparatively, aims to know the influence of usage of learning media based on Flash against the achievements of learning to read students of class X SMK Negeri 1 Sewon. Descriptive research results (1) the tendency of the learning achievement read students of class X SMK Negeri 1 Sewon used learning media based on PowerPoint including high; (2) which used learning media based on Flash including very high. In comparative there a difference a significant achievement of students learning to read students of class X SMK Negeri 1 Sewon between lessons that used learning media based on Flash and media based on PowerPoint.